Comparative LCA of ultrasound-assisted extraction of polyphenols from chicory grounds under different operational conditions. (20th September 2018) - Vauchel, Peggy; Colli, Carolina; Pradal, Delphine; Philippot, Maeva; Decossin, Stéphane; Dhulster, Pascal; Dimitrov, Krasimir
Abstract: Different innovative technologies have emerged in the last decades in the field of extraction processes and are commonly considered as green extraction processes. This work aimed at investigating on the environmental performances of one of these technologies, namely ultrasound assisted extraction, using the recognized life cycle assessment (LCA) methodology. The proposed case study was an ultrasound-assisted extraction process for the valorization of antioxidant polyphenols from chicory grounds (food industrial by-product), which could find applications as natural antioxidants in food and cosmetic industries. A comparative LCA was carried out with a functional unit defined as obtaining 0.55 L of extract exhibiting 220 μmol Trolox equivalent antioxidant capacity. This enabled to evaluate variation of environmental impacts as a function of operating conditions. Increasing temperature implied important raise on all impact categories. Use of ethanol in the solvent implied huge increase of impacts, which moderated gains on extraction yield, and pointed out the importance of including environmental impacts criteria as well as productivity and economic criteria while optimizing processes, in the view of tending to more sustainable solutions. Ultrasounds assistance enabled a general reduction of environmental impacts. Hence, this study confirmed (using the recognized LCA tool) environmental benefits of ultrasound assisted extraction. Highlights: Comparative LCA on antioxidant phenolics extraction from chicory waste was performed. Effect of operating conditions on the process environmental performance was studied. Use of ethanolic solvent appeared as a hotspot. US assistance enabled environmental impacts reduction up to 25%. Optimal conditions regarding LCA: ambient temperature, water solvent, US assistance.